The LaBelle mitochondrial plasmid of Neurospora intermedia encodes a novel DNA polymerase that may be derived from a reverse transcriptase. - Schulte, U (1991)
The LaBelle-1b strain of Neurospora intermedia contains a 4.1-kb closed-circular mitochondrial plasmid DNA, which encodes a single long open reading frame of 1,151 amino acids reported to have sequence similarity to reverse transcriptases. Here, we show that the LaBelle strain contains a novel DNA polymerase activity that is highly specific for the endogenous LaBelle plasmid DNA in nucleoprotein particles and can be distinguished from the mitochondrial DNA polymerase by several characteristics. Photolabeling experiments indicate that the LaBelle-specific DNA polymerase activity is associated with a polypeptide of 120 kDa, which is in good agreement with the size predicted for the protein encoded by the LaBelle plasmid open reading frame (132 kDa). This 120-kDa polypeptide is found only in the LaBelle strain that contains the mitochondrial plasmid, and it cosegregates with mitochondria in sexual crosses, suggesting that it is encoded by the plasmid. The LaBelle-specific DNA polymerase efficiently uses the artificial DNA substrates, poly(dA)-oligo(dT) and poly(dC)-oligo(dG), but despite its reported sequence similarity to reverse transcriptases, it has very low activity with analogous RNA substrates, poly(rA)-oligo(dT), poly(rC)-oligo(dG), or poly(rCm)-oligo(dG). Considered together with the previous sequence comparisons, our results suggest that the LaBelle plasmid encodes a novel DNA polymerase, which was derived from a protein that was at one time a reverse transcriptase but lost its ability to use RNA templates. This DNA polymerase now presumably functions in replication of the plasmid. Our results constitute the first biochemical evidence for a DNA polymerase activity associated with a mitochondrial plasmid. Further, they may provide insight into the evolution of DNA polymerases from reverse transcriptases, as presumably occurred in the course of evolution following the transition from the so-called RNA world to the present DNA world.